Enterotoxin Production of Bacillus thuringiensis Isolates From Biopesticides, Foods, and Outbreaks - Johler, Sophia; Kalbhenn, Eva M.; Heini, Nicole; Brodmann, Peter; Gautsch, Sylvia; Bağcioğlu, Murat; Contzen, Matthias; Stephan, Roger; Ehling-Schulz, Monika (Frontiers in Microbiology, 2018)
While the relevance of Bacillus (B.) cereus as a major cause of gastroenteritis is undisputed, the role of the closely related B. thuringiensis in foodborne disease is unclear. B. thuringiensis strains frequently harbor enterotoxin genes. However, the organism has only very rarely been associated with foodborne outbreaks, possibly due to the fact that during outbreak investigations, B. cereus is routinely not differentiated from B. thuringiensis. A recent EFSA scientific opinion stresses the urgent need for further data allowing for improved risk assessment, in particular as B. thuringiensis is a commonly used biopesticide. Therefore, the aim of this study was to gain further insights into the hazardous potential of B. thuringiensis. To this end, 39 B. thuringiensis isolates obtained from commercially used biopesticides, various food sources, as well as from foodborne outbreaks were characterized by panC typing, panC-based SplitsTree analysis, toxin gene profiling, FTIR spectroscopic analysis, a cytotoxicity assay screening for enterotoxic activity, and a sphingomyelinase assay. The majority of the tested B. thuringiensis isolates exhibited low (23%, n = 9) or mid level enterotoxicity (74%, n = 29), and produced either no (59%, n = 23) or low levels (33%, n = 13) of sphingomyelinase, which is reported to act synergistically with enterotoxins Nhe and Hbl. One strain isolated from rosemary was however classified as highly enterotoxic surpassing the cytotoxic activity of the high-level reference strain by a factor of 1.5. This strain also produced vast amounts of sphingomyelinase. Combining all results obtained in this study into a fingerprint pattern, several enterotoxic biopesticide strains were indistinguishable from those of isolates from foods or collected in association with outbreaks. Our study shows that many B. thuringiensis biopesticide strains exhibit mid-level cytotoxicity in a Vero cell assay and that some of these strains cannot be differentiated from isolates collected from foods or in association with outbreaks. Thus, we demonstrate that the use of B. thuringiensis strains as biopesticides can represent a food safety risk, underpinning the importance of assessing the hazardous potential of each strain and formulation used.